PENGELOLAAN ZAKAT DI BADAN AMIL ZAKAT NASIONAL KABUPATEN TULUNGAGUNG DALAM PERSPEKTIF MAQASHID AL-SYARIAH - Aibak, Kutbuddin (IAIN Tulungagung, 2016)
Why BAZ cannot operate optimally is due to two factors. First, as amatter of fact, this institution is just passively waiting for the zakatpayers. Second, the zakat paid through this institution is limited tothe zakat of income from certain offices, not from massive individual.In addition, it has been a long tradition that the Moslems do not paytheir zakat fithrah through this institution. Zakat fithrah is commonlypaid for the receivers’ daily consumption. Considering the problemsabove, some initiatives must be taken. First, institutionally BAZmust be empowered by setting up zakat picking units (UPZ) in everymosque and these units are managed professionally to serve thezakat payers. Second, the zakat must be managed and distributed tothe right receivers for the productive purposes, not the consumptivepurposes. Since the zakat is still distributed for the consumptivepurposes, from the perspective of maqashid al syariah it can beconcluded that the management of zakat so far has not yet achievedits fundamental purpose to empower and to prosper the poors andthe weaks.Kata kunci: Pengelolaan, Pengumpulan dan Pendistribusian Zakat,Maqashid al-Syariah